Student Activity Sheets based on Scientific and Problem Based Learning (PBL) in the Introduction to Microeconomics course: How and Why? - Retno Mustika Dewi (MO.RI Publishing, 2022)
Economics is the study of how humans choose and create wealth. Through economics, humans can think and make decisions in allocating their resources appropriately. The limited availability of the variety of questions used in microeconomics courses has encouraged researchers to compile scientific-based Student Activity Sheets (LKM) and Problem Based Learning (PBL). The purpose of this study is to describe (1) feasibility, (2) effectiveness, and (3) practicality of developing scientific-based Student Activity Sheets (LKM) and Problem Based Learning (PBL) in the Introduction to Microeconomic Theory course. This type of research is development research. using the Borg and Gall (1983) model. The trial subjects in this development research were students of the economic education study program. The results showed that the percentage of development feasibility was 94% in the very feasible category, the percentage of effectiveness showed that students obtained a learning mastery score above 75% in the effective and complete category, and the practicality percentage obtained a score of 99.5 in the practical category. It can be concluded that the development of the Student Activity Sheet is feasible to apply.